Spółdzielcze prawo do lokalu jako prawo osobowo-majątkowe - Krzekotowska, Krystyna (Wydział Prawa i Administracji UAM, 1984)
The article presents cooperative right to living quarters with a due regard paid to social function of housing rights designed to fulfill needs of family. It is expressed in subordination of traditionally property-like elements of housing rights to legal-family relations. As a result, the housing rights, as the institution of alimentation, can be contained neither in a category of property rights, nor in a category of personal rights. Consequently, taking personal and property rights into consideration in the general theory of civil law was deemed advisable. Personal or family-personal element has its weight in forming property rights, especially in socialism. It is manifested in the regulations ref ering to a new and stable form of socialist property-personal property. In the scope of housing relations it consists in regulating rights of spouses in a wider context beyond general principles of property relations in matrimony. The cooperative right to living quarters assigned in the duration of matrimony belongs to both spouses. Cessation of statutory community of property in the duration of matrimony does not terminate community of that right. The community can be dissolved only by court on demand of one of the spouses. Lease relations in turn, are included in the compulsory community of spouses in housing regulations, it is the case of lease which originated before conclusion of matrimony as well. The right formed in that manner can be in service of whole family as long as it exists as a whole or in a reduced state (e.g. for a reason of divorce). There is no objection to have that right assigned after divorce to the spouse children remain with- Not uniform regulation of a right to living quarters after spouse's death in cooperative law and in housing regulation is presented next. Including housing rights to a general category of personal-property rights would eliminate various regulations refering to sociologically uniform situations. Rights of that type would enjoy a uniform treatement dictated by housing interests of family.
Cooperative right to living quarters as a personal and property right